Management of pharmacotherapy‐related problems in acute coronary syndrome: Role of clinical pharmacist in cardiac rehabilitation unit. Issue 1 (1st April 2019) - Casper, Eman Ahmed; El Wakeel, Lamiaa Mohamed; Saleh, Mohamed Ayman; El‐Hamamsy, Manal Hamed
Abstract: Acute coronary syndrome (ACS) is one of the leading causes of mortality worldwide and negatively impacts healthcare costs, productivity and quality of life. Polymorbidity and polypharmacy predispose ACS patients to medication discrepancies between cardiologist‐prescribed medication and drug use by the patient, drug‐related problems (DRPs) and inadequate drug adherence. This study aimed to evaluate the impact of clinical pharmacist–provided services on the outcome of ACS patients. This was a prospective, randomized, controlled study on ACS patients participating in a cardiac rehabilitation programme. Forty ACS patients were randomly assigned to either control group, who received standard medical care, or intervention group, who received standard medical care plus clinical pharmacist–provided services. Services included DRP management, clinical assessment and enforcing the patient education and adherence. For both groups, the following were assessed at baseline and after 3 months: DRPs, adherence (assessed by 8‐item Morisky Adherence Questionnaire), patient's knowledge (assessed by Coronary Artery Disease Questionnaire), 36‐Short Form Health Survey (SF‐36), heart rate, systolic and diastolic blood pressure, low‐density lipoprotein (LDL), total cholesterol (TC) and fasting blood glucose (FBG). After 3 months, there was a significant difference between the intervention and control groups in the per cent change of DRPs (median: −100 vs 5.882, P = 0.0001), patient's adherence score (median: 39.13 vs −14.58, P = 0.0001), knowledge score (median: 30.28 vs −5.196, P = 0.0001), SF‐36 scores, heart rate (mean: −10.04 vs 6.791, P = 0.0001), diastolic blood pressure (mean: −17.87 vs 10.45, P = 0.0001), systolic blood pressure (mean: −16.22 vs 4.751, P = 0.0001), LDL (median: −25.73 vs −0.2538, P = 0.0071), TC (median: −14.62 vs 4.123, P = 0.0005) and FBG (median: −11.42 vs 5.422, P = 0.0098). Clinical pharmacists can play an important role as part of a cardiac rehabilitation team through patient education and interventions to minimize DRPs.